Implementasi Model Pembelajaran Kolaboratif Hafalan pada Mata Kuliah Hadits Tarbawi di Universitas Nahdlatul Ulama Indonesia - Fitriani, Nur (Journal of Education and Culture, 2025)
The learning model is one of the important reasons for achieving learning objectives. Therefore, choosing the right learning model for students is a rote collaborative learning model in the tarbawi hadith course. This research is intended to provide an overview of implementation the collaborative memorization model in the tarbawi hadith course for students of the UNUSIA Islamic Religious Education study program. The research was prepared using a descriptive qualitative approach. Data was collected using observation, interviews and documentation, then the analysis technique used the Miles and Huberman technique, namely summarizing the data, presenting the data, and providing conclusions. Findings from the implementation of the collaborative model in memorizing hadiths related to education, secondly progressing in groups to memorize hadiths and thirdly evaluation by lecturers.